2014
DOI: 10.4238/2014.august.25.12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control and estimation of genetic parameters for seed-coat darkening of carioca beans

Abstract: ABSTRACT. The maintenance of the light color of the grains of carioca beans is a requirement for the development of new cultivars of common beans because it enables the storage of grains for long periods so that they may be traded at a proper opportunity. Crosses of cultivar BRSMG Madrepérola, which presents slow grain darkening, were made to 10 elite lines presenting normal darkening to obtain information about the genetic control of the trait and estimates of phenotypic and genotypic parameters. Progenies at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
41
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 12 publications
4
41
1
1
Order By: Relevance
“…This can be explained by the fact that some genotypes darken in a more accentuated way over time, a trait that cannot be observed in newly harvested seeds. In general, there was an increase in the mean values for bean seed coat darkening over storage time, as also reported in the studies of Silva et al (2014) and Alvares et al (2016).…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…This can be explained by the fact that some genotypes darken in a more accentuated way over time, a trait that cannot be observed in newly harvested seeds. In general, there was an increase in the mean values for bean seed coat darkening over storage time, as also reported in the studies of Silva et al (2014) and Alvares et al (2016).…”
Section: Resultssupporting
confidence: 84%
“…Results from ANOVA of the two trials for phenotypic evaluation of the 17 common bean lines shown significant differences among them, regardless of seed coat storage time. The results confirm that only 45 d of storage is already sufficient to differentiate lines regarding bean seed darkening (Silva et al, 2008; Silva et al, 2014). The scores obtained at 90 and 135 d of storage were identical, and consequently, the results of ANOVA were equal in these storage periods.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations